Capacity for sustainment of recently established syringe service programs in Appalachian Kentucky: The central role of staff champions. (3rd February 2022) - Cooper, Hannah L. F.; Gross, Skylar; Klein, Emma; Fadanelli, Monica; Ballard, April; Lockard, Scott; Batty, Evan; Young, April; Ibragimov, Umed
Abstract: Introduction: Ensuring adequate harm reduction infrastructure in rural areas is imperative, as drug‐related epidemics expand into them. Here, we explore the capacity for sustainment of syringe service programs (SSP) in Appalachian Kentucky. Methods: We interviewed all staff ( n  = 16) of all SSPs ( n  = 7) in two Kentucky health districts in 2018–2019 using semi‐structured one‐on‐one qualitative interviews; local departments of health (DOH) operated the SSPs. Interview domains encompassed: (i) SSP establishment; (ii) day‐to‐day operations, participation and health impacts; (iii) perceived prospects for sustainment; and (iv) perceived influences on #i–#iii. We analysed verbatim transcripts using thematic analytic methods; Schell's 'capacity for sustainment' constructs were treated as sensitising concepts during the analysis. Results: Most community members, law enforcement and DOH staff opposed SSPs before they opened, because of stigma and concerns about enabling and needlestick injuries; DOH staff also opposed SSPs because they believed they lacked the capacity to operate them. Training, technical assistance, visible evidence of the programs' public health impact and contact with SSP participants transformed DOH staff into program champions. As champions, SSP staff developed programs that had strong capacity for sustainment, as defined by Schell (e.g. visible public health impact, stable funding, political support). Staff reported that the SSPs had high prospects for sustainment. Discussion and Conclusion: As in SSPs that opened in cities decades ago, staff in emerging SSPs in these rural areas appear to have become crucial champions for these controversial programs, and may serve as vital resources for expanding harm reduction programming more broadly in these underserved areas.